ChemInform Abstract: The Nematic Phases of Bent‐Core Liquid Crystals. Issue 33 (19th August 2014) - Gleeson, Helen F.; Kaur, Sarabjot; Goertz, Verena; Belaissaoui, Abdel; Cowling, Stephen; Goodby, John W.
Abstract Review: 54 refs.